Assembling Phenothiazine into a Porous Coordination Cage to Improve Its Photocatalytic Efficiency for Organic Transformations. Issue 49 (9th November 2022) - Lin, Hengyu; Xiao, Zhifeng; Le, Khoa N.; Yan, Tian‐hao; Cai, Peiyu; Yang, Yihao; Day, Gregory S.; Drake, Hannah F.; Xie, Haomiao; Bose, Riya; Ryan, Conor A.; Hendon, Christopher H.; et al.
Abstract: Photo‐catalysis by small‐molecules is often limited by catalyst degradation and low electron‐transfer efficiency. Herein we report a stable N‐phenyl‐phenothiazine (PTH)‐derived porous coordination cage (PCC) as a highly efficient photocatalyst. By the incorporation of the photocatalytic PTH moiety into a PCC, aggregation‐induced quenching (AIQ) was shown to be reduced. An improvement in catalyst stability was discovered, ascribed to the synergistic effects of the PTH moieties. The catalyst, operating through a photolytic single‐electron transfer, was utilized for photo‐catalyzed dehalogenation and borylation. Evaluation of the catalytic mechanism in the borylation reaction showed that the improved performance results from the more efficient formation of the electron donor‐acceptor (EDA) complex with the cage. This discovery provides a potential strategy to improve the photophysical properties and stabilities of small‐molecule organic photocatalysts via supramolecular chemistry. Abstract : Porous coordination cages (PCCs) are known for their strong intermolecular interaction and high stability for homogeneous catalysis. In this work, a photo‐active molecule, PTH, was assembled into PCC‐40, which showed excellent photocatalytic performance in dehalogenation and photo‐borylation. The synergistic effect of multi catalytic centers was studied. The results may provide future directions for improvement of a large group of photocatalysts.